Effect of ulinastatin on the inflammatory response after video-assisted thoracic lobectomy in patients with lung cancer: a randomized controlled study. Issue 7 (5th April 2022) - Hwang, Won Jung; Joo, Min A.; Joo, Jin
Abstract: Background: The first-line treatment for lung cancer is surgical resection, and one-lung ventilation (OLV) is the most basic anesthetic management method in lung surgery. During OLV, inflammatory cytokines are released in response to the lung tissue damage and promote local and contralateral lung damage through the systemic circulation. We designed a randomized, prospective study to evaluate the effect of the urinary trypsin inhibitor (UTI) ulinastatin on the inflammatory response after video-assisted thoracic lobectomy in patients with lung cancer. Methods: Adult patients aged 19 to 70 years, who were scheduled for video-assisted thoracic lobectomy surgery to treat lung cancer between May 2020 and August 2020, were enrolled in this randomized, prospective study. UTI (300, 000 units) mixed with 100 mL of normal saline in the ulinastatin group and 100 mL of normal saline in the control group was administered over 1 h after inducing anesthesia. Results: The baseline (T0) interferon- γ (IFN- γ)/interleukin-4 (IL-4) ratio was not different between the groups (6941.3 ± 2778.7 vs. 6954.3 ± 2752.4 pg/mL, respectively; P   >  0.05). The IFN- γ/IL-4 ratio was significantly higher in ulinastatin group at 30 min after entering the recovery room than control group (20, 148.2 ± 5054.3 vs. 6674.0 ± 2963.6, respectively; adjusted P  < 0.017). Conclusion: Administering UTI attenuated the anti-inflammatory response, in terms of INF-γ expression and the IFN- γ/IL-4 ratio, after video-assisted thoracic surgery in lung cancer patients. Trial registration: Clinical Research Information Service of Korea National Institute of Health (CRIS), KCT0005533.